2010
DOI: 10.1111/j.1477-2574.2010.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Unresectable pancreatic adenocarcinoma: do we know who survives?

Abstract: A simple and clinically meaningful point-based symptom score can successfully predict survival in patients with UPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
1
11
0
2
Order By: Relevance
“…Müller et al 27 found that American Society of Anesthesiologists score, the presence of liver metastasis, pain, CA19-9, and carcinoembryonic antigen levels were independent predictors of poor survival in patients undergoing bypass surgery for GOO due to pancreatic cancer. Finally, Jamal et al 29 proposed a McGill-Brisbane score based on weight loss of more than 10% of body weight, pain, jaundice, and smoking as a predictor of survival to tailor palliative treatment. However, given that the majority of these studies investigated factors predictive of overall survival rather than post-stent placement survival, the findings may not be perfectly relevant to our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Müller et al 27 found that American Society of Anesthesiologists score, the presence of liver metastasis, pain, CA19-9, and carcinoembryonic antigen levels were independent predictors of poor survival in patients undergoing bypass surgery for GOO due to pancreatic cancer. Finally, Jamal et al 29 proposed a McGill-Brisbane score based on weight loss of more than 10% of body weight, pain, jaundice, and smoking as a predictor of survival to tailor palliative treatment. However, given that the majority of these studies investigated factors predictive of overall survival rather than post-stent placement survival, the findings may not be perfectly relevant to our patients.…”
Section: Discussionmentioning
confidence: 99%
“…If patients were not reported as deceased, they were censored on 14 February 2011, allowing a minimum of 14‐month follow‐up for the last patients included in this study. The primary outcome of this study was mortality at 9 months, a clinically significant endpoint based on previous studies . Overall survival was also assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Upon presentation, 80% of patients have locally advanced or metastatic disease and are not immediate surgical candidates . Predicting survival in patients who have resectable and unresectable PAC is a crucial step in optimizing personalized patient management …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their model included weight loss more than 10%, jaundice, pain and smoking and was able to discriminate those with worse life expectation better than imaging. Weight loss >10% was the best independent predictor of low survival providing 38% of the final score [20].…”
Section: Cachexia and Survivalmentioning
confidence: 97%